2006
DOI: 10.1051/0004-6361:20053851
|View full text |Cite
|
Sign up to set email alerts
|

An absolutely calibrated survey of polarized emission from the northern sky at 1.4 GHz

Abstract: A new polarization survey of the northern sky at 1.41 GHz is presented. The observations were carried out using the 25.6 m telescope at the Dominion Radio Astrophysical Observatory in Canada, with an angular resolution of 36 . The data are corrected for ground radiation to obtain Stokes U and Q maps on a well-established intensity scale tied to absolute determinations of zero levels, containing emission structures of large angular extent, with an rms noise of 12 mK. Survey observations were carried out by drif… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

17
266
1

Year Published

2006
2006
2013
2013

Publication Types

Select...
6
4

Relationship

3
7

Authors

Journals

citations
Cited by 185 publications
(284 citation statements)
references
References 22 publications
17
266
1
Order By: Relevance
“…Actually, the complete high-polarisation Fan region stretches out over (l, b) ≈ (90 • −190 • , −5 • −25 • ) and therefore also encompasses the Ghosh field. Indeed, Wolleben et al (2006) argue from depolarisation arguments that the Fan region has to extend (Bernardi et al 2009), and GMRT (Ghosh et al 2012) estimates of the outer scale of turbulence of the Galaxy towards the second Galactic quadrant with earlier observations from Ohno & Shibata (1993), Clegg et al (1992), Haverkorn et al (2008), Malkov et al (2010), and. The turbulence scale derived by Fletcher et al (2011) and Beck et al (1999) for the nearby spiral galaxies M 51 and NGC 6946 respectively are also shown.…”
Section: Discussionsupporting
confidence: 57%
“…Actually, the complete high-polarisation Fan region stretches out over (l, b) ≈ (90 • −190 • , −5 • −25 • ) and therefore also encompasses the Ghosh field. Indeed, Wolleben et al (2006) argue from depolarisation arguments that the Fan region has to extend (Bernardi et al 2009), and GMRT (Ghosh et al 2012) estimates of the outer scale of turbulence of the Galaxy towards the second Galactic quadrant with earlier observations from Ohno & Shibata (1993), Clegg et al (1992), Haverkorn et al (2008), Malkov et al (2010), and. The turbulence scale derived by Fletcher et al (2011) and Beck et al (1999) for the nearby spiral galaxies M 51 and NGC 6946 respectively are also shown.…”
Section: Discussionsupporting
confidence: 57%
“…Wolleben (2007) modelled the NPS as two local shells based mainly on DRAO 1.4 GHz all-sky polarization survey data (Wolleben et al 2006). However, this polarization survey suffers strong depolarization for latitudes below about 30 • , which prevents the tracking of the NPS towards low latitudes.…”
Section: The Southern North Polar Spur Extensionmentioning
confidence: 99%
“…Also it will be crucial to analyse microwave data together with ancillary data from radio and infrared frequencies. 4 During the final phase of the revision process of this work, the DRAO 1.4 GHz polarization survey has been released (Wolleben et al 2006). The data are available at http://www.mpifr-bonn.mpg.de/div/konti/26msurvey/ or http://www.drao-ofr.hia-iha.nrc-cnrc.gc.ca/26msurvey/ or http://cdsweb.u-strasbg.fr/cgi-bin/qcat/?J/A+A/448/411.…”
Section: Introductionmentioning
confidence: 99%